Pengaruh Edukasi Masyarakat, Promosi Produk, Dan Pelayanan Terhadap Kepercayaan Nasabah Untuk Menabung Di BMT (KJKS) Al – Falah Batanghari - Wasito, Galih Hadi; Yateno, Yateno (Jurnal Manajemen DIVERSIFIKASI, 2022)
Lack of knowledge or education makes people less understanding about Islamic financial services. Coupled with a modest promotion, and less extensive. Services that are also not improved will hinder the development of business progress. The success of a service production, will depend on how the customer assesses it, namely from the sense of trust that has been formed. If the customer has put his trust in a company, it is difficult for the customer to move to another financial institution, so that it can be mutually beneficial for both parties, namely the financial institution and its customers. Thus, this study aims to determine the effect of public education on customer confidence in saving at BMT KJKS Al - Falah Batanghari, (2) Knowing the effect of product promotion on customer confidence in saving at BMT KJKS Al - Falah Batanghari, (3) Knowing the effect of service on customer trust to save at BMT KJKS Al – Falah Batanghari. This type of research is quantitative research, with a sample or questionnaire method. The sample obtained by accidental sampling obtained as many as 50 respondents. While the data analysis technique of this research is using multiple linear regression through parial t test, simultaneous f test and the determinant coefficient R2. The results of this study indicate that (1) public education on customer trust in saving at BMT (KJKS) Al - Falah Batanghari has a positive and significant effect, from the results of the t-test to get a t-value ofcount 3.159 > ttable 1.679, (2) product promotion towards customer trust to save at BMT (KJKS) Al - Falah Batanghari has a positive and significant influence, from the results of the t test to get a value and tcount of 3,869 > ttable 1,679, (3) service on trust has a positive and significant effect, from the results of the t test get the value of tcount 4,589 > ttable 1,679. The conclusion, simultaneously that the three independent variables have a good role on customer confidence to save at BMT (KJKS) Al - Falah Batanghari by obtaining aF value ofcalculated 176,430 > Ftable 2.810, and the magnitude of the coefficient of determination is 0.920 or 92.0% which means 8% is influenced by other variables. It is recommended to BMT (KJKS) Al - Falah Batanghari to provide education to the community, increase promotions, and better services so that the public or customers are more interested, enthusiastic, and believe in saving.